Barriers to reporting guideline adherence in point-of-care ultrasound research: a cross-sectional survey of authors and journal editors. Issue 4 (22nd January 2021) - Prager, Ross; Gagnon, Luke; Bowdridge, Joshua; Unni, Rudy R; McGrath, Trevor A; Cobey, Kelly; Bossuyt, Patrick M; McInnes, Matthew D F
Abstract : Objective: Although the literature supporting the use of point-of-care ultrasound (POCUS) continues to grow, incomplete reporting of primary diagnostic accuracy studies has previously been identified as a barrier to translating research into practice and to performing unbiased systematic reviews. This study assesses POCUS investigator and journal editor attitudes towards barriers to adhering to the Standards for Reporting of Diagnostic Accuracy Studies (STARD) 2015 guidelines. Design, setting, participants: Two separate surveys using a 5-point Likert scale were sent to POCUS study investigators and journal editors to assess for knowledge, attitude and behavioural barriers to the complete reporting of POCUS research. Respondents were identified based on a previous study assessing STARD 2015 adherence for POCUS studies published in emergency medicine, anaesthesia and critical care journals. Responses were anonymously linked to STARD 2015 adherence data from the previous study. Written responses were thematically grouped into the following categories: knowledge, attitude and behavioural barriers to quality reporting, or other. Likert response items are reported as median with IQRs. Main outcome measures: The primary outcome was the median Likert score for the investigator and editor surveys assessing knowledge, attitude and behavioural beliefs about barriers to adhering to the STARD 2015 guidelines. Results: The investigator survey response rate was 18/69 (26%) and the editor response rate was 5/21 (24%). Most investigator respondents were emergency medicine practitioners (13/21, 62%). Two-thirds of investigators were aware of the STARD 2015 guidelines (12/18, 67%) and overall agreed that incomplete reporting limits generalisability and the ability to detect risk of bias (median 4 (4, 5)). Investigators felt that the STARD 2015 guidelines were useful, easy to find and easy to use (median 4 (4, 4.25); median 4 (4, 4.25) and median 4 (3, 4), respectively). There was a shared opinion held by investigators and editors that the peer review process be primarily responsible for ensuring complete research reporting (median 4 (3, 4) and median 4 (3.75, 4), respectively). Three of 18 authors (17%) felt that the English publication language of STARD 2015 was a barrier to adherence. Conclusions: Although investigators and editors recognise the importance of completely reported research, reporting quality is still a core issue for POCUS research. The shared opinion held by investigators and editors that the peer review process be primarily responsible for reporting quality is potentially problematic; we view completely reported research as an integral part of the research process that investigators are responsible for, with the peer review process serving as another additional layer of quality control. Endorsement of reporting guidelines by journals, auditing reporting guideline adherence during the peer review process and translation of STARD 2015 guidelines into additional languages may improve reporting completeness for the acute POCUS literature. Trial registration number: Open Science Framework Registry (https://osf.io/5pzxs/ ).